PENGARUH PROFESIONALISME GURU DAN PERHATIAN ORANG TUA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN KELAS XI DI SMA NEGERI 5 PEMATANGSIANTAR TAHUN AJARAN 2024/2025 - Rumanty Anastasya Marpaung; Sepriandison Saragih; Marthin Fransisco Manihuruk (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine whether there is an influence of teacher professionalism and parental attention on student learning achievement in the subject of civic education for class XI at SMA Negeri 5 Pematangsiantar in the 2024/2025 Academic Year.The next step is testing the hypothesis by calculating the linear regression equation, namely Y over is X1= 74,76 + 0,117 X1, meaning that between variable X1 is linear with Y and Y over X2 = 75,70 + 0,1 X2, meaning that between variable X2 is linear with Y and Y over X1 and X2 is = 0.85 + 3.03 X1 + 2.01 X2, meaning that between variables X1 and X2 are linear with Y.he coefficients of influence obtained are as follows: (1) The contribution coefficient of Y on X1 is 35.45% (2) The contribution coefficient of Y on X2 is 38.68% (3) The contribution coefficient of X1 on X2 is 76.15% (4) The contribution coefficient of Y on X1 and X2 is 50.09%.Based on the hypothesis test, namely the significant influence test (t-test) by rejecting H0 and accepting H1, it is obtained: 1. The influence of Teacher Professionalism on Student Learning Achievement in Civic Education Subjects for Class XI at SMA Negeri 5 Pematangsiantar in the 2024/2025 academic year is